Evaluation of potential productivity in coniferous forests by integrating field data and aerial laser scanning in Hidalgo, México - Rodrigo Ramos-Madrigal; Héctor M. de los Santos-Posadas; José René Valdez-Lazalde; Efraín Velasco-Bautista; Gregorio Ángeles-Pérez; Alma Delia Ortiz-Reyes (Forest Systems)
Aim of study: To predict the productivity potential of a managed conifer forest by estimating the site index from Light Detection and Ranging (LiDAR) data.